Heavy Metals Pollution Assessment in Soil of Al-Zubair area, Southern Iraq (Iraqi National Journal of Earth Science (INJES), 2023)
Mn>Zn>Cr>Ni>Pb>Cu>As>Co>Cd. Based on Igeo and PI values, the results obtained high pollution levels for both Cd and Zn, especially in Kut Al-Markaz, Al-Faraha, and Al-Thoahrat stations respectively, whereas IPI indicates low to moderate levels. On the other hand, EF of heavy metals was in decreasing order: EFCo>EFCd>EFAs>EFPb>EFZn>EFNi>EFCu>EFCr>EFMn. Generally, the pollution of Al-Zubair soil was attributed to anthropogenic sources like the industrial emission of the Al-Shuaiba oil Refinery, oil exploration processes, vehicle emissions in the center of the city as well as the waste of petrochemical company nearby Al-Zubair city]]>
Keywords: Heavy metals,,; ,،,؛Integrated pollution index,,; ,،,؛Geoaccumulation index,,; ,،,؛Al-Zubair,,; ,،,؛Enrichment factor